2020
DOI: 10.3390/pr8111466
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Dehydration by Extractive Distillation with Use of Aminoethers of Boric Acid

Abstract: Aminoethers of boric acid (AEBA) were studied as potential extractants for the separation of aqueous–alcoholic azeotropic mixtures by extractive distillation. The conditions of vapor–liquid equilibrium in aqueous solutions of ethanol and isopropanol in the presence of AEBA were studied. The division of AEBA molecules into group components was proposed, and previously unknown geometric parameters of the boron group and the energetic pair parameters of the boron group with the alkane group, ether group, amine-3d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 27 publications
1
11
0
Order By: Relevance
“…These polyurethane membranes were obtained by crosslinking AEBA and diphenylmethane diisocyanate (MDI). Figure 1 shows AEBA from which the polyurethanes were synthesized [ 24 , 25 ]. The AEBA molecule was synthesized from triethanolamine, boric acid, and polyethylene glycol in a molar ratio of 1:6:12.…”
Section: Methodsmentioning
confidence: 99%
“…These polyurethane membranes were obtained by crosslinking AEBA and diphenylmethane diisocyanate (MDI). Figure 1 shows AEBA from which the polyurethanes were synthesized [ 24 , 25 ]. The AEBA molecule was synthesized from triethanolamine, boric acid, and polyethylene glycol in a molar ratio of 1:6:12.…”
Section: Methodsmentioning
confidence: 99%
“…The first case study considers the dehydration of ethanol, an essential and often investigated separation [2,[53][54][55] that shows significant similarity to isopropanol dehydration. It is of great importance in the production of bioethanol, which, in combination with biodiesel, accounts for 90% of the applied biofuels [56] and for which the global production is expected to reach about 145 billion liters by 2023 [57].…”
Section: Ethanol Dehydrationmentioning
confidence: 99%
“…The papers [49,50] presented the results of studying the properties of amino esters of boric acid (AEBA) synthesized using boric acid, triethanolamine, and various glycols and triols (Figure 1). In this article, glycols and triols used in the synthesis of AEBA are referred to as AEBA-MEG (monoethylene glycol), AEBA-DEG (diethylene glycol), AEBA-TEG (triethylene glycol), AEBA-GL (glycerol).…”
Section: Introductionmentioning
confidence: 99%
“…The advantage of AEBA-MEG/TEG/DEG/GL in comparison with ILs is the ease of synthesis and the availability of the reagents used for the synthesis. The studies carried out in [49,50] showed the promise of using AEBA-TEG/DEG for the extractive distillation of an ethanol-water mixture. The purpose of this work is to carry out further studies of AEBA as highly effective entrainers for the separation of azeotropic mixtures of acetonitrile-water and acetonitrile-ethanol-water.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation